Sub-national sovereignties? : territory, authority and regulation in three sites of "xenophobic" violence in South Africa - Monson, Tamlyn Jane (My University, 2011)
This study investigates the nature of territory, identity and political authority in three areas affected by the May 2008 violence against foreign nationals and other outsiders in South Africa: Itireleng (Laudium), ‘Beirut’ (Alexandra), and Madelakufa II (Tembisa). The study compares the three territorial orders from the perspective of nodal governance, using a typology of state‐government and informal nodes, each with dimensions of authority and provision, and asks whether they may constitute local sovereign forms (sub‐national sovereignties). The study finds a different micropolitical geography in each case study: in Itireleng, informal nodes of governance gained control over the means of movement and were locally viewed as legitimate, indicative of a localised sovereign form. In Beirut, Alexandra, an ‘accidental local sovereignty’ emerged when informal nodes attempted to supplement formal state controls but found themselves on the wrong side of the law. In Madelakufa II, violence was seen as illegitimate, criminal behaviour, and the state sovereignty was strengthened by the repressive response of formal state‐government nodes (in the form of the police). The three cases illustrate that, while the state remains empirically significant, and state citizenship retains a resonance that contributes to the production of local forms of exclusion, the functional dimension, as well as the authority of the state over certain jurisdictions, varies substantially across spaces within South Africa.